2014
DOI: 10.1017/s0950268814002131
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and the risk of infection with other intracellular bacteria: a population-based study

Abstract: SUMMARY Persons who develop tuberculosis may have subtle immune defects that could predispose to other intracellular bacterial infections (ICBIs). We obtained data on tuberculosis and five ICBIs (Chlamydia trachomatis,Salmonella spp., Shigella spp., Yersinia spp., and Listeria monocytogenes) reported to the Tennessee Department of Health, USA, 2000–2011. Incidence rate ratios (IRRs) comparing ICBIs in persons who developed tuberculosis and ICBIs in the Tennessee population, adjusted for age, sex, race and ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, an American population-based study found no difference in the risk of the ICBIs Salmonella spp, Yersinia spp, and Listeria monocytogenes in persons who developed TB vs. those in the general population, and found there were actually fewer Chlamydia trachomatis infections observed within the first year post-TB diagnosis compared to the non-TB population. Extrapulmonary TB was linked to a higher rate of salmonella infections compared to pulmonary TB but all 8 patients with salmonellosis and TB were also HIV co-infected (158).…”
Section: Other Important Bacteriamentioning
confidence: 99%
“…However, an American population-based study found no difference in the risk of the ICBIs Salmonella spp, Yersinia spp, and Listeria monocytogenes in persons who developed TB vs. those in the general population, and found there were actually fewer Chlamydia trachomatis infections observed within the first year post-TB diagnosis compared to the non-TB population. Extrapulmonary TB was linked to a higher rate of salmonella infections compared to pulmonary TB but all 8 patients with salmonellosis and TB were also HIV co-infected (158).…”
Section: Other Important Bacteriamentioning
confidence: 99%
“…There are a number of systems used to classify the responses, the Ryan system published in 2005 being that used by the American College of Pathologists (Table 1) [14]. Other factors have been studied which may also help forecast the survival of patients and help determine the best treatment [15][16][17][18][19]. Some of these are pathological such as lympho-vascular invasion and perineural infiltration while others are clinical factors such as the carcinoembryonic antigen (CEA) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Other factors have been studied which may also help forecast the survival of patients and help determine the best treatment [15][16][17][18][19]. Some of these are pathological such as lympho-vascular invasion and perineural infiltration while others are clinical factors such as the carcinoembryonic antigen (CEA) [15][16][17]. Our objective was to evaluate the effect of the response (pCR) in survival of the patients with locally advanced rectal carcinoma treated with surgery and neoadjuvant chemo-radiotherapy and the pattern of recurrence in this subgroup of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Persons who develop tuberculosis may have subtle immune defects that could predispose them to other intracellular bacterial infections in the same patient. 22 The susceptibility to tuberculosis is considered to be genetically inherited. 23 24 It has been a common experience of the author as well as many clinicians that patients, especially children, who are prone to recurrent upper and lower respiratory affections, often have a family history of Tuberculosis.…”
Section: Discussionmentioning
confidence: 99%